Pengaruh Media Pembelajaran Digital Unity Berbasis Augmented Reality Terhadap Hasil Belajar Matematika Siswa Kelas V Sekolah Dasar - Wardani, Emilia Kusuma; Sari, Elok Fariha (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – The development of digital technology has encouraged innovation in the world of education, especially in the use of more interactive and engaging learning media. Interactive Unity media is considered adequate for improving student learning outcomes on the volume of cubes and beams. This study aims to (1) to analyze the completeness of student learning outcomes on the volume of cubes and beams, (2) to determine the difference in participant learning outcomes using Unity learning media and without using Unity learning media, (3) to determine the effectiveness of using Unity learning media on student learning outcomes.Method – This study uses quantitative research. The research method is quasi-experimental, and the research design is a non-equivalent control group design. The subjects of this study included 2 schools with a total of 52 fifth-grade students. Data collection techniques used observation, interviews, and tests. The instruments used were observation sheets, teaching modules, and pre-test and post-test questions. Findings – The study showed that the learning outcomes of students using unity media on the volume material of cubes and beams were declared complete exceeding the KKTP determined as evidenced by the results of the t test> t table (3.598> 1.0931). There is a significant difference in the learning outcomes of the experimental group and the control group with a two-sided significance value of p (<0.000) <? (0.05). In addition, the N-gain analysis showed that the increase in learning outcomes of experimental class students was higher at 67.17% compared to the control class of only 22.43%. Research Implications – These findings indicate the need for utilizing interactive digital media in mathematics learning to help students understand concepts more visually. With this research, it is expected to be a recommendation for educators in the teaching and learning process that is innovative and effective in learning mathematics.